Cooperative Learning, Responsibility, Ambiguity, Controversy and Support in Motivating Students - Ronald Brecke; Jacy Jensen (Park University, 2007)
This paper argues that student motivation is nurtured more by intrinsic rather than extrinsic rewards. Rather than relying on grades alone to stimulate students, this paper explores how engendering a natural critical learning environment can give students a sense of ownership in their own learning and lead to their commitment to that learning. We examine uses of cooperative learning, shared responsibility, ambiguity, controversy and support in student motivation.